2016
DOI: 10.1007/s41109-016-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Walls-in-one: usage and temporal patterns in a social media aggregator

Abstract: The continual launches of new online social media that meet the most varied people’s needs are resulting in a simultaneous adoption of different social platforms. As a consequence people are pushed to handle their identity across multiple platforms. However, due the to specialization of the services, people’s identity and behavior are often partial, incomplete and scattered in different “places”. To overcome this identity fragmentation and to give an all-around picture of people’s online behavior, in this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It is known that human interactions do not occur at a constant rate. They rather show a bursty character with a non-Poissonian inter-event time distribution that reflects a memory from past interactions [34][35][36][37][38][39] www.nature.com/scientificreports/ interactions or state updating. "Aging" is one form of memory effect on which the rate of interactions depends on the persistence time of an agent in a state, modifying the transition to a different state [40][41][42] .…”
mentioning
confidence: 99%
“…It is known that human interactions do not occur at a constant rate. They rather show a bursty character with a non-Poissonian inter-event time distribution that reflects a memory from past interactions [34][35][36][37][38][39] www.nature.com/scientificreports/ interactions or state updating. "Aging" is one form of memory effect on which the rate of interactions depends on the persistence time of an agent in a state, modifying the transition to a different state [40][41][42] .…”
mentioning
confidence: 99%
“…The introduction of aging is motivated by strong empirical evidence that human interactions do not occur at a constant rate and cannot be described using a Markovian assumption. Empirical studies have reported heavy-tail inter-event time distributions that reflect heterogeneous temporal activity patterns in social interactions [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…This rate dependence on the persistence times accounts for the observation that human interactions do not occur at a constant rate. They rather show a bursty character with a non-Poissonian inter-event time distribution [37][38][39][40][41][42]. However, most social simulations, including simulations of variants of the Schelling model, implicitly assume a constant rate of interactions or state updating.…”
Section: Introductionmentioning
confidence: 99%